Protracted Hydrogeological Activity in Arabia Terra, Mars: Evidence From the Structure and Mineralogy of the Layered Deposits of Becquerel Crater. Issue 9 (21st September 2022) - Schmidt, G.; Luzzi, E.; Rossi, A. P.; Pondrelli, M.; Apuzzo, A.; Salvini, F.
Abstract: The formation of layered mounds on Mars remains a major topic of debate, with the relationship between their deposition and chemical alteration a major aspect still to be constrained. The association these deposits have with hydrated minerals indicates aqueous processes were active in their past, however the extent and duration of this aqueous period has yet to be fully realized. We studied compositional, stratigraphical, and structural characteristics of two separate layered deposits within Becquerel crater, Arabia Terra, to constrain their origins and the intensity of past aqueous activity. We find that due to key differences in composition, layering, and deformation between the two deposits, the timing of important depositional changes within Becquerel can be identified. We propose a scenario involving differences in fluid expulsion intensity and water level between the two layered deposits, in which diverse depositional and post‐depositional environments were able to form. Furthermore, internal collapsing and deformation of the main mound might reflect that fluid upwelling persisted below the mound after formation. Determining the relationship between these two deposits is an important step in unraveling the past climate of Arabia Terra, and more broadly Mars. The evidence of protracted fluid expulsion represents a unique opportunity for future missions searching for signs of past life. Plain Language Summary: Becquerel crater is located in the Arabia Terra region (Mars), and it is characterized by the occurrence of a large layered mound. We used spectral reflectance to study mineralogy within the layered mound, finding hydrated sulfates, minerals which formed in the presence of water. In addition, we noticed that not far from the mound, there are separate layered deposits within a smaller interior crater on the floor of Becquerel crater. This interior crater creates nearly a kilometer difference in elevation between the large layered mound and the separate layered deposits, leaving the separate layered deposits mostly isolated from the rest of Becquerel. The layered deposits within the interior crater were found to have unique clay lithologies. We compared these separate layered deposits with those of the large layered mound to determine their relationship and we concluded that their origins might be related to fluid expulsion which exploited weak areas of the crater floor from the intersections of impact related radial faults and a pre‐existing regional fault. Due to the abundance of fluvial related structures and hydrated mineral assemblages, Becquerel might be considered an optimal place to search for signs of past life. Key Points: Spectral and morphologic analyses highlight multiple events related to water activity within Becquerel crater Widespread faulting suggests the internal collapse of a layered mound, possibly due to fluid expulsion from below Differences in elevation reflect different mineralogies and layer thicknesses between two layered deposits